Addressing incontinence for people with dementia living at home: a documentary analysis of local English community nursing service continence policies and clinical guidance. Issue 3 (13th July 2012) - Drennan, Vari M; Norrie, Caroline; Cole, Laura; Donovan, Sheila
<x xml:space="preserve">Abstract</x> Aim and objectives. To establish whether the problems and issues experienced by people with dementia living at home and their carers were addressed in the clinical guidance for continence management for community nursing services in England. Background. Internationally, the numbers of people with dementia are rising. Managing incontinence is a significant issue as the presence of incontinence is one of the triggers for people with dementia to move their residence to a care home. People with dementia living at home and their family carers report difficulties in accessing knowledgeable professionals and acceptable continence products. Design. A review by documentary analysis of clinical policies and guidance from a sample of community nursing services in all Strategic Health Authority regions of England. Methods. A sample of clinical policy and guidance documents for continence assessment and management from up to four community nursing services in each of the ten Strategic Health Authority regions in England was sought. Documentary analysis was undertaken on the relevance of the documents identified for people with dementia living at home. Findings. Ninety‐eight documents from 38 local community nursing services spread across ten Strategic Health Authority areas were obtained and analysed. Only in the documents of three services were nurses offered detailed guidance about the management of incontinence for people with dementia at home. In the documentation of only one service were people with dementia identified as a special case which warranted the provision of additional continence products. Conclusion. Clinical guidance on continence assessment and management for community nurses in many parts of England does not address the specific needs of people with dementia living at home or their carers. Relevance for clinical practice. Nurses working in community settings and those providing clinical leadership in continence care should review their clinical guidance and policies to ensure relevance for people with dementia living at home and their family carers.